HDAC6 and CXCL13 Mediate Atopic Dermatitis by Regulating Cellular Interactions and Expression Levels of miR-9 and SIRT1 - Kwon, Yoojung; Choi, Yunji; Kim, Misun; Jeong, Myeong Seon; Jung, Hyun Suk; Jeoung, Dooil (Frontiers in Pharmacology, 2021)
Histone deacetylase 6 (HDAC6) has been known to regulate inflammatory diseases. The role of HDAC6 in allergic skin inflammation has not been studied. We studied the role of HDAC6 in atopic dermatitis (AD) and the mechanisms associated with it. The decreased expression or chemical inhibition of HDAC6 suppressed AD by decreasing autophagic flux and cellular features of AD. AD increased expression levels of the Th1 and Th2 cytokines, but decreased expression levels of forkhead box P3 (FoxP3) and interleukin-10 (IL-10) in an HDAC6-dependent manner. CXC chemokine ligand 13 (CXCL13), which was increased in an HDAC6-depenednt manner, mediated AD. MiR-9, negatively regulated by HDAC6, suppressed AD by directly regulating the expression of sirtuin 1 (SIRT1). The downregulation or inhibition of SIRT1 suppressed AD. Experiments employing culture medium and transwell suggested that cellular interactions involving mast cells, keratinocytes, and dermal fibroblast cells could promote AD; HDAC6 and CXCL13 were found to be necessary for these cellular interactions. Mouse recombinant CXCL13 protein increased HDAC6 expression in skin mast cells and dermal fibroblast cells. CXCL13 protein was found to be present in the exosomes of DNCB-treated skin mast cells. Exosomes of DNCB-treated skin mast cells enhanced invasion potentials of keratinocytes and dermal fibroblast cells and increased expression levels of HDAC6, SIRT1 and CXCL13 in keratinocytes and dermal fibroblast cells. These results indicate that HDAC6 and CXCL13 may serve as targets for the developing anti-atopic drugs.